Validation of Hv1 channel functions in BV2 microglial cells using small molecule modulators - Ashutosh Sharma; Ashutosh Sharma; Nandini B. Kale; Priyanka Yadav; Priyanka Yadav; Shivani Yadav; Shivani Yadav; Madhavi Ranawat; Madhavi Ranawat; Valmik S. Shinde; Valmik S. Shinde; Aravind Singh Kshatri; et al. (Frontiers in Cellular Neuroscience)
Microglia are the first responders to insults or damages in the brain where they display both beneficial and detrimental effects. Excessively activated microglia aggravate the secondary damage by producing several proinflammatory mediators. Voltage-gated proton channels, Hv1 are selectively expressed in the microglia where they modulate microglial activation. Therefore, Hv1 has emerged as a tractable target for treating a number of conditions, ranging from pain, neurological disorders to cancer. Due to the absence of a suitable Hv1 inhibitor, the pathophysiological roles of Hv1 channels has been exemplified using preclinical Hv1 knockout (KO) mice models. Thus, we characterized and validated the microglial Hv1 channel’s functions using the recently reported Hv1 inhibitor (YHV98-4) and a novel Hv1 activator (S-023-0515) in a model of lipopolysaccharide (LPS)-induced neuroinflammation. In LPS-stimulated BV2 microglial cells, treatment with YHV98-4 alleviated the proinflammatory cytokines such as TNF-α, IL-6, and iNOS. Direct activation of Hv1 channels using S-023-0515 resulted in an increase in microglial M1 like polarisation, proinflammatory mediators, phagocytic capacity and mitochondrial ROS levels but did not alter the cellular ROS production. Analysis of the signalling pathway indicated that YHV98-4 and S-023-0515 exerted their protective and deleterious effects, respectively via phosphorylation of NF-κΒ, which serves as an upstream regulator of the inflammatory cascade. Collectively, our results elucidate the essential role of Hv1 channels in microglial functions and also demonstrate that their pharmacological inhibition and activation during inflammatory conditions are neuroprotective or neurotoxic, respectively.